Metode Langsung dalam Pembelajaran Sekar raré pada Pertunjukan Jangér Sakral Banjar Kedaton Desa Adat Sumerta - Bagus Angga, I Made Bagus Angga Putra; I Made Gede Anadhi; Putu Eddy Purnomo Arta (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
The existence of Jangér in Banjar Kedaton remains well-preserved to this day. The Jangér songs in Banjar Kedaton, Desa Adat Sumerta, possess distinctive characteristics, values, and unique qualities in both their melodies and performances. Despite various training methods being employed for Jangér songs, their effectiveness has been found lacking. Consequently, trainers have concluded that the Direct Method is the most effective teaching approach. This study addresses three research questions: (1) the application of the Direct Method in teaching sekar raré for Jangér performances, (2) the challenges encountered when implementing this method, and (3) strategies to overcome these challenges. The aim of this research is to provide insights to dancers, trainers, researchers, and government institutions about the Direct Method. Using a qualitative approach and the theories of Behaviorism and Constructivism, this study finds that the application of the Direct Method faces obstacles such as the availability of trainers, dancers' skills, and training time. Mention the Proposed solutions, among others include encouraging dancers to practice Jangér songs more at home.